Low-voltage digitally controlled current differencing buffered amplifier - Prasertsom, Danucha; Tangsrirat, Worapong; Surakampontorn, Wanlop (My University, 2008)
A low-voltage digitally controlled current differencing buffered amplifier (DC-CDBA) is proposed. The realization scheme is through the cascade connection of a current differencing circuit, a current division network (CDN) and a buffered voltage amplifier. To achieve the digital control of the current gain of the circuit, a novel CDN is also proposed. The proposed DC-CDBA can operate with the low supply voltage of ±1.25V. PSPICE simulations using standard 0.5μ CMOS process parameters are in agreement with the theory. © 2008 IEEE.